Relationship of Cellular Components to the Stability of Concentrated Lactic Streptococcus Cultures at -17 C - Gilliland, S. E. (1974)
Concentrated cultures of lactic streptococci varied with respect to survival at -17 C. Cells of each strain grown at pH 6.0 were more stable to freezing than were those grown statically. The lipid fraction of the cells from static cultures was important in preventing death during freezing. As the percentage of octadecenoic acid in the cellular lipids from different cultures increased, the percentage of survivors decreased. Capsular material associated with cells from cultures grown both statically and at pH 6.0 was also important in protecting the cells at -17 C. The amount of capsular material, measured as percentage of cellular glucose, varied among the cultures tested. Cultures containing larger amounts of the capsular material were more resistant to the stress of freezing than those containing low levels.